The Orthodox Church and the Transhumanist Ideas on Overcoming Death - Cira, Călin Emilian (Diakrisis, 2021)
For mankind, death is a great mystery. Throughout history, numerous opinions about death have been issued, in search of its cause, and many ways and means to defeat it have been attempted. Recent scientific developments have not stayed back from the challenge of studying biological life and attempting technological solutions to help people reach an advanced age that is not subject to decrepitude, and perhaps even to achieve immortality. This idea is also present in the transhumanist movement that aims to change human nature through technology and supports the possibility of obtaining a lifespan capable of far exceed the current one. In this text, we attempt to give a possible answer to this transhumanist challenge from an orthodox Christian point of view.